Competing a Family Language Policy in Two Generations of Transnational Families in Indonesia: A Case Study - Mauziyyah, Meka; Setyaningsih, Endang; Sumardi, Sumardi (JOLLT Journal of Languages and Language Teaching, 2024)
Transnational families in Indonesia currently still have many difficulties in developing and creating an ideology of language use that they implement in their families, with a variety of languages to maintain their family’s ethnic identity. This research explores three research questions, as follows. (1) How did parents perceive the roles of various languages in shaping their children’s future? (2) What languages were used in the family? This research finds the choice of language use within the context of Indonesian transnational families with different ethnic backgrounds. Employing a qualitative approach with a case study design (Yin, 2014), this study employs 2 participants, a woman, and her mother, both of them are scholarship awardees, who negotiate language ideologies, practices, and policies within their families among linguistic diversity and transnational mobility. Through thematic analysis (Saldana, 2012) of data collection from semi-structured interviews and observation, revealed several initial, open, and axial codes. This finding of this research reveals 1). The differences ideology between two generation. 2). The family’s efforts to balance maintaining English and Bahasa Indonesia language. The implication of this study is made for the language policy maker and other transnational parent. Â In conclusion, this study highlights the complexities of language use in transnational families and demonstrates that these families face challenges and opportunities in creating an environment that supports language learning.